Projected clinical benefit of surveillance imaging for early detection and treatment of breast cancer metastases. Issue 1 (12th December 2018) - O'Dell, Walter; Takita, Cristiane; Casey‐Sawicki, Katherine; Daily, Karen; Heldermon, Coy D.; Okunieff, Paul
Abstract: This article presents current best knowledge to assess the projected outcomes benefit of adding multi‐modality surveillance imaging to standard follow‐up care for breast cancer patients at high risk (>30%) for developing future metastases. This analysis is motivated by recent preliminary clinical studies that have suggested that augmenting systemic treatment of early‐stage metastases with targeted surgery and/or radiosurgery achieves significant overall survival and disease‐free survival benefit. Our primary aims are to: (a) describe the clinical motivation and scan parameters needed to identify the early onset of metastatic progression in breast cancer patients for effective surgical or radiosurgical treatment; (b) estimate the anticipated survival benefit for high‐risk patients under this recommended protocol; and (c) estimate the radiation risks associated with the repeated body imaging of this protocol.